Pilot study on jetting pre-oxidation fluidized bed gasification adapting to caking coal - Zhao, Z.; Zhang, J.; Zhang, G.; Zeng, X.; Zhao, F.; Dong, Li; Xu, G. (Elsevier, 2013)
Caking coal is difficult to be gasified in fluidized bed (FB) because of the inevitable particle agglomeration caused by caking in the dense bottom of the bed. Literature studies have shown that pre-oxidizing the coal can suppress its caking propensity, while quick dispersion of coal particles, for example, by gas jetting in the plastic stage of heating is critical to such a suppression of the caking agglomeration. Thus, the so-called jetting pre-oxidation fluidized bed gasification (JPFBG) is devised in this study to gasify caking coal in FB. Coal particles usually below 5mm are blown into the space above the bottom dense bed surface by an O 2 -containing gas jet to disperse and meanwhile to pre-oxidize the particles. The resulting char particles with little, even without caking propensity fall into the dense bottom of the bed to allow their gasification there. After validating the destruction of caking agglomeration by jetting pre-oxidation in a laboratory FB apparatus, a 150kg/h pilot JPFBG plant was built and the coal with the caking index of about 20 was successfully gasified in this plant using normal air and O 2 -enriched air. The heating vale of the produced gas varied in 2.9-5.0MJ/mN3 and decreased with raising the oxygen percentage applied to the jet feeding. Raising the oxygen percentage for the jet caused more of the produced gas formed in the bottom dense bed of char gasification to burn off in the jetting zone. The optimal proportion of the oxygen applied to the jet feeding or coal pre-oxidation was found to be about 37% against the total oxygen supply. Enriching the O 2 content in the gasification agent to about 30vol.% enhanced greatly the gasification rate of the tested low-reactivity coal in JPFB. © 2013 Elsevier Ltd.